Concurrent injection of dexamethasone intravitreal implant and anti-angiogenic agent in patients with macular edema: A retrospective cohort study. Issue 47 (November 2017) - Lin, Hung-Yu; Lee, Chia-Yi; Huang, Jing-Yang; Yang, Shun-Fa; Chao, Shih-Chun
Abstract : Abstract: To evaluate the safety and efficiency in macular edema patients who concurrently received a single injection of a dexamethasone intravitreal implant (DEX, 0.7 mg) and ranibizumab (2.3 mg). A retrospective cohort study was conducted, and medical records from 2012 to 2016 were reviewed. Patients who received concurrent DEX and ranibizumab injections with a follow-up period of at least 3 months were enrolled in the study group. An age and gender-matched group received ranibizumab injections and was designated the control group. The best-corrected visual acuity (BCVA), central macular thickness (CMT) and intraocular pressure (IOP) were included in the analysis. Steroid-induced ocular hypertension (SIOH) is defined as either an elevation of more than 10 mmHg from baseline or a single IOP measurement of more than 30 mmHg. A total of 26 patients were enrolled in the current study with 13 patients in each group. Both the BCVA ( P  = .04) and CMT ( P  < .01) achieved significant improvement after the follow-up period in the study group. The IOP increased after the injection but no significant elevation was observed throughout the follow-up period in the study group ( P  = .15). For SIOH, 1 patient in the study group had an elevated IOP of 10 mmHg (7.7%) at 2 postoperative months, and no single IOP measurement of more than 30 mmHg was obtained. Five patients (38.5%) in the study group received medical treatment that successfully retarded their IOP elevation, and no individuals required surgical management. In the control group, there were no significant fluctuations concerning BCVA, CMT, and IOP, and no ocular hypertension was observed. According to the inter-group analysis, the CMT and BCVA recovered more significantly in the study group than in the control group. Concurrent injection of DEX and ranibizumab is a preliminary method that shows effectiveness in treating ME. Furthermore, safety is also guaranteed, with moderate levels of severity and transient IOP elevation being observed. A future large-scale study is necessary to evaluate the long-term effects and safety of this combined treatment.